Morphological and Genetic Diversity of Opisthosporidia: New Aphelid Paraphelidium tribonemae gen. et sp. nov. (23rd August 2016) - Karpov, Sergey A.; Tcvetkova, Victoria S.; Mamkaeva, Maria A.; Torruella, Guifré; Timpano, Hélène; Moreira, David; Mamanazarova, Karomat S.; López‐García, Purificación
Abstract: Aphelids are a poorly known group of parasitoids of algae that have raised considerable interest due to their pivotal phylogenetic position. Together with Cryptomycota and the highly derived Microsporidia, they have been recently re‐classified as the Opisthosporidia, which constitute the sister group to the fungi within the Holomycota. Despite their huge diversity, as revealed by molecular environmental studies, and their phylogenetic interest, only three genera have been described ( Aphelidium, Amoeboaphelidium, and Pseudaphelidium ), from which 18S rRNA gene sequences exist only for Amoeboaphelidium and Aphelidium species. Here, we describe the life cycle and ultrastructure of a new representative of Aphelida, Paraphelidium tribonemae gen. et sp. nov., and provide the first 18S rRNA gene sequence obtained for this genus. Molecular phylogenetic analysis indicates that Paraphelidium is distantly related to both Aphelidium and Amoebaphelidium, highlighting the wide genetic diversity of aphelids. Paraphelidium tribonemae has amoeboflagellate zoospores containing a lipid‐microbody complex, dictyosomes, and mitochondria with rhomboid cristae, which are also present in trophonts and plasmodia. The amoeboid trophont uses pseudopodia to feed from the host cytoplasm. Although genetically distinct, the genus Paraphelidium is morphologically indistinguishable from other aphelid genera and has zoospores able to produce lamellipodia with subfilopodia like those of Amoeboaphelidium .